2016
DOI: 10.1159/000452255
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Discriminability and Response Bias Indices for the Evaluation of Recognition Memory in Mild Cognitive Impairment and Alzheimer Disease

Abstract: Background: Most studies examining episodic memory in Alzheimer disease (AD) have focused on patients' impaired ability to remember information. This approach provides only a partial picture of memory deficits since other factors involved are not considered. Objective: To evaluate the recognition memory performance by using a yes/no procedure to examine the effect of discriminability and response bias measures in amnestic mild cognitive impairment (a-MCI), AD dementia, and normal-aging subjects. Methods: We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Response bias B" was not previously examined in bvFTD, but Russo et al (2017) report a significantly lower discriminative ability and a liberal response bias in patients with AD, which is highly similar to our findings in the AD group. The lack of a difference in response bias between bvFTD and AD found in our study appears counterintuitive, but the (slightly) liberal response bias that was present in both patients groups (but not in controls) is in line with previous findings in patients with dementia (Beth et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Response bias B" was not previously examined in bvFTD, but Russo et al (2017) report a significantly lower discriminative ability and a liberal response bias in patients with AD, which is highly similar to our findings in the AD group. The lack of a difference in response bias between bvFTD and AD found in our study appears counterintuitive, but the (slightly) liberal response bias that was present in both patients groups (but not in controls) is in line with previous findings in patients with dementia (Beth et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…One can hypothesize that differences in memory performance in bvFTD and AD change with disease progression and accompanying atrophy of frontal and temporal brain areas. For example, it is hypothesized that frontal/dysexecutive impairment in AD increases as the disease progresses (Russo et al, 2017), which may result in a larger (liberal) response bias and a potential larger between-group difference. The mean age of the AD patients was relatively young (68.1 ± 7.2 years) with an MMSE score of 22.7 ± 4.6 indicating a substantial number of early-onset cases and a relatively mild disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies simplify recognition task by only registering the number of correct identifications (hits), without the inclusion of false alarms in their interpretation. Based on the signal detection theory, a discriminability recognition index (d-prime) can be calculated including both hits and false alarms (Russo et al, 2016). In addition, d-prime has been shown to distinguish healthy older adults from those with a-MCI or mild AD.…”
Section: Introductionmentioning
confidence: 99%
“…A neuroimaging study conducted by Moradi et al (2017) found that the MRI-based volumetric features were suitable variables for predicted parts of the RAVLT tool using an elastic net-based linear regression model. Russo et al (2017) found that parts of the RAVLT assessment can have differences in discrimination accuracy and response bias between MCI and AD subjects, indicating there could be diagnostic specificity if using different test portions.…”
Section: Discussionmentioning
confidence: 99%